RbSyn: type- and effect-guided program synthesis. - Guria, Sankha Narayan.; Foster, Jeffrey S.; Van Horn, David. (Tufts University. Tisch Library., 2023)
Keywords: Ruby, program synthesis, type and effect systems.; Topic: Software and its engineering / Software creation and management / Software development techniques / Automatic programming; ACM Open.